Direct estimates of food and eating production function parameters for 2004-12 using an ATUS/CEX synthetic dataset - Tamar Khitarishvili; Fernando Rios-Avila; Kijong Kim (Levy Economics Institute of Bard College, 2015)
This paper evaluates the presence of heterogeneity, by household type, in the elasticity of substitution between food expenditures and time and in the goods intensity parameter in the household food and eating production functions. We use a synthetic dataset constructed by statistically matching the American Time Use Survey and the Consumer Expenditure Survey. We establish the presence of heterogeneity in the elasticity of substitution and in the intensity parameter. We find that the elasticity of substitution is low for all household types.
Keywords: C14; D13; J22; 330; Consumption Expenditures; Elasticity of Substitution; Food Production; Household Production; Statistical Matching; Time Use